The Biocentric Theory as a Foundation to Protect Nature from the Impact of Business Activity - Camacho Vinueza, Daniela (2023)
After the negative impacts and the destruction generated by humans and large corporations to the environment, it has been necessary that from a socio-legal perspective the developing of an effective protection of nature, avoiding irreversible damages, and controlling the effects of climate change. Hence, to address these issues under one theory that focuses mainly on recognizing the environment that surrounds the life of the human being, while observing it as subjects of rights, that is, also observing the protection and conservation of nature that surrounds it as a subject of rights is indispensable. Nature is seen as means of habitat and life, therefore the close connection it has with the human being is also observed in terms of effective protection by the States. Such a theory can serve to guarantee and protect both the rights of human beings as well as the protection of the surroundingenvironment according to the acquired obligations related to the satisfaction and protection of the rights, and compliance with international goals and obligations in terms of sustainable development and actions to combat climate change by the States. Likewise, through the global mandates agreed upton from a biocentric approach, what would be generated is greater protection and safeguarding of the environment, recognizing the general need to protect nature as a subject of rights, recognizing it as thefundamental source of human life.